The Effect of Institutional Ownership, Fiscal Loss Compensation, and Accounting Conservatism on Tax Avoidance - Kenny Ardillah; Yohanes Halim (Journal of Accounting Auditing and Business, 2022)
This research intends to examine the impact of institutional ownership, fiscal loss compensation, and accounting conservatism on tax avoidance in mining companies listed on the Indonesia Stock Exchange. The sample collection procedure used is purposive sampling. The sample of this research is mining companies listed on the Indonesia Stock Exchange from 2016-to 2019. Procedure analysis was used in this research is multiple linear regression. The research findingsindicateno effect of institutional ownership, fiscal loss compensation, and accounting conservatism on tax avoidance. The implications of this research are to provide information for management to make decisions by considering the impact of each decision taken if the company implements tax avoidance policies and provide information for investors in assessing the factors that can influence companies to practice tax avoidance.